2022
DOI: 10.1002/kjm2.12520
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA small nucleolar RNA host gene 16 reduces sepsis‐induced myocardial damage by regulating miR‐421/suppressor of cytokine signaling 5 axis

Abstract: Currently, sepsis‐induced cardiomyopathy (SIC) remains as one of the most critical clinical syndromes in terminally ill patients. Noncoding RNAs (including microRNAs and long noncoding RNAs) are implicated in both the onset and development of SIC. We herein investigated the functional role and molecular target of long noncoding RNA small nucleolar RNA host gene 16 (SNHG16) in an in vitro SIC model of H9c2 myocardial cells. We used lipopolysaccharide (LPS) as endotoxin to treat H9c2 cells to mimic SIC damages. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…SOCS family proteins are a class of negative regulators of JAK2-STAT3 signaling pathway, consisting of SOCS1-7, both containing Src-homology domian and a conserved C-termial domain [ 46 ]. Among them, SOCS5 is expressed in a variety of adult tissues, playing anti-inflammatory, anti-tumor, anti-oxidative stress and other functions [ 16 , 47 , 48 ]. Xi et al uncovered that salidroside could promote SOCS5 transcription to reduce airway inflammation and airway remodeling in asthmatic mice [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SOCS family proteins are a class of negative regulators of JAK2-STAT3 signaling pathway, consisting of SOCS1-7, both containing Src-homology domian and a conserved C-termial domain [ 46 ]. Among them, SOCS5 is expressed in a variety of adult tissues, playing anti-inflammatory, anti-tumor, anti-oxidative stress and other functions [ 16 , 47 , 48 ]. Xi et al uncovered that salidroside could promote SOCS5 transcription to reduce airway inflammation and airway remodeling in asthmatic mice [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that inhibiting SOCS5 significantly promoted cigarette extract-induced inflammatory responses, exacerbating COPD progression [ 17 ]. It also shown that maintaining SOCS5 expression could reduce LPS-induced oxidative stress and inflammation and improve myocardial injury [ 16 ]. Here, we established a COPD mouse model, whose results further verified that overexpression of SOCS5 inhibited JAK2/STAT3 pathway activation, improved lung function and reduced oxidative stress in COPD mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation